Study On The Production Of Ecoenzimes From Market Waste Raw Materials - Anggi Indah Yuliana; Ana Mariatul Khiftiyah; Mohamad Nasiruddin (AGARICUS: Advances Agriculture Science & Farming, 2023)
Market waste is a component of organic waste that has not been widely used. One of the efforts to utilize market waste is to use market waste as a raw material for making ecoenzymes. This study aims to describe the characteristics of the color, pH, aroma, and total dissolved solids (TDS) of ecoenzymes produced from market waste including mustard greens, kale, banana peels, pineapple peels, and various combinations of these market wastes. Ecoenzyme fermentation was carried out for 90 days. The results of the observations showed that there were differences in color, pH, aroma, and TDS in the resulting ecoenzymes. The color of the ecoenzyme produced is generally brown with different color degradation. The aroma of the ecoenzymes produced also varies, but ecoenzymes containing banana peels, as well as a combination of fruit and vegetable peels, apart from the treatment of banana peels + kale, produce an unpleasant odor. The pH of the ecoenzyme produced was entirely acidic with a pH range of 2.9-5.6. The lowest ecoenzyme pH was made from kale + mustard greens, while the highest pH was made from banana skin treatment. Ecoenzyme TDS values ​​also varied, with the lowest value being 955 in the banana peel treatment, and the highest value in the mustard greens treatment with a value of 2920. The results showed that market waste has the potential to be used as a raw material for making ecoenzymes.